Emerging self-directed learning strategies in the digital age - Giuseffi, Frank G. (IGI Global, 2018)
"This book explores where education is heading in terms of Self-Directed Learning and the way individuals seek and learn information in the Digital Age. It assists educators in examining the importance of educational goals that focus on transformational learning experiences, reflection and how these activities are being influenced by the digital world we are now living in"--